2010
DOI: 10.1039/b921432a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of protic ionic liquids with minimal water content and 15N NMR study of proton transfer

Abstract: Low-molecular-weight Brønsted acids and amine bases were used to reproducibly prepare very dry, high-purity room-temperature protic ionic liquids (PILs). A series of eight amine bases and six Brønsted acids were combined to produce 48 mixtures, of which 18 were liquid at room temperature. The phase transitions and thermal decomposition temperatures were determined for each mixture; whereas viscosity, density and conductivity were determined for the room-temperature liquids. By utilising (15)N NMR it was possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
149
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 42 publications
8
149
1
1
Order By: Relevance
“…Nevertheless, by increasing the added water in a PIL, presenting originally a non-Newtonian shear thinning behavior, Burrell et al showed that the flow behavior of the mixture changes from nonNewtonian shear thinning to Newtonian and then from Newtonian to non-Newtonian shear thickening. 49,50 Altin et al 56 have reported, in the case of the Newtonian IL 1-ethyl-3-methyl ethylsulfate, that depending on the concentration of Fe 2 O 3 particles in this IL the flow behavior of the mixture can change also from Newtonian to nonNewtonian shear thinning and shear thickening.…”
Section: Rheological Properties Of Selected Pils and Mixturesmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, by increasing the added water in a PIL, presenting originally a non-Newtonian shear thinning behavior, Burrell et al showed that the flow behavior of the mixture changes from nonNewtonian shear thinning to Newtonian and then from Newtonian to non-Newtonian shear thickening. 49,50 Altin et al 56 have reported, in the case of the Newtonian IL 1-ethyl-3-methyl ethylsulfate, that depending on the concentration of Fe 2 O 3 particles in this IL the flow behavior of the mixture can change also from Newtonian to nonNewtonian shear thinning and shear thickening.…”
Section: Rheological Properties Of Selected Pils and Mixturesmentioning
confidence: 99%
“…In fact, non-Newtonian behavior has been described for several AILs and PILs. [46][47][48][49][50] For example, Seddon et al 46 have shown that the alkylimidazolium tetrafluoroborate family (number of carbon atoms is typically 12) is thixotropic fluids whose viscosity decreases when increasing the shear rate. Kulkarni et al 48 have reported that the flow behavior may change from Newtonian to non-Newtonian by increasing the alkyl chain length on the cation like alkyl-methylimidazoliumbased AILs.…”
Section: Rheological Properties Of Selected Pils and Mixturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Protic ILs, triethylammonium methylsulphonate (TAMS), EDAA and EDAF, were synthesized according to the procedure described before 36 . Briefly, the base solution (for example, triethylamine and ethylenediamine) and the acid solution (for example, methylsulphonic acid, acetic acid and formic acid) were purified, dried and handled under inert gas atmosphere.…”
Section: Discussionmentioning
confidence: 99%